Inhibition of Adhesion of Staphylococcus Bacteria on Mesh Implants in Combination with Biocides (in vitro) - M. V. Kuznetsova; A. A. Parshakov; E. V. Afanasyevskaya; V. A. Samartsev (Антибиотики и Химиотерапия)
The adhesion of Staphylococcus aureus ATCC® 25923 and the clinical strains of S.aureus, S.epidermidis on monofilament surgical mesh implants - macroporous polyester and microporous polypropylene in combination with biocides was assessed in an in vitro experiment. Staphylococcus cells adhered to the surface of implant fragments without treatment with biocides within a few hours, and there was no significant effect on the adhesion of the structure or chemical composition of the fiber. Short-term exposure of implants to the solutions of amoxiclav (100 μg/ml) and chlorhexidine (0.5%) led to inhibition of bacterial growth and contamination of the surface for at least two days. In the experiment with vancomycin (100 μg/ml), bacterial cells adhered on the surface of the mesh fragments after 24 h, but their amount was significantly lower than in the control group. It was noted that both implants in combination with chlorhexidine were not contaminated with S.aureus bacteria for 2 days under conditions of a high concentration of cells in the suspension. Regulation of bacterial adhesion using biocidal solutions can be a simple and economical strategy to combat the development of infection in the field of surgical intervention.